Educa????o a dist??ncia: propostas pedag??gicas e tend??ncias dos cursos de gradua????o - Pino, Adriana Soeiro (2017)
The Distance Education Courses have grown in Brazil for several reasons, among them: lower costs, flexibility of schedules, quality of technological resources. Nowadays, with the high unemployment rates in Brazil in 2016-2017, and the need for continued formation and aca-demic education to maintain or to get a job, they make the University degree courses, espe-cially those that offered in the distance modalities, a great option for busy citizens and for people who needs flexible schedules to study. It is clear that the costs of this type of educa-tion are lower, because students don???t have transportation costs, nor a classroom at Universi-ties, so educational Institutions investing less in building infrastructure and virtual student can study at home. In this context, the growth of the distance modality is impressive, but we still have many challenges ahead, since many students of this modality are not ???digital natives??? and they tend to give up the courses because of technological problems and adjustment on the pedagogical model. According to data from the latest EAD Census BR 2015, there are 5,048,912 students enrolled in the modality, that is 1,180,296 more students registered than in 2014. The dropout rates are also high, they are ranging from 26% to 50%, however, Distance Education is already part of the educational context of the 21st century and this modality has recently been contributing to some of its strategies and digital tools iin face-to-face teaching, since the profile of students has also changed rapidly and, in the near future, they will be more familiar with technological devices, and with interactive activities,that will provide the inte-gration of modalities: blended learning. In time of changes, the institutional challenges are many: pedagogical, technological and even in the adjustment of business model. This study investigated the pedagogical approach and the structure of digital courses, tutor??s models and the impact of regulatory changes for the sector. The purpose of this study is to analyze two undergraduate courses: one from a private univer-sity and another from a public college institution, in order to of current legislation, identifying their respective methodologies and strategies, which guided the structuring of their courses, in order to Analyze the theoretical bases that support the diverse and varied practices in the area. Also check what tools are available in their Learning Management System ??? LMS and how they help the learning process in this new millennium.